A simple method for generating small calcium-alginate beads by syringe. (December 2014) - Delbari, Ali; Fadaei, Fatemeh; Salehi, Mohammad; Farahani, Reza Mastery; Piryaei, Abbas; Heidari, Mohammad Hassan; Nourozian, Mohsen; Mansouri, Vahid
<x content-type="archive" xml:space="preserve">Abstract</x> Currently, cell microencapsulation (CM) is a promising technology for a wide range of areas of interest in cellular and molecular biology. This technique can be used for large-scale cell culture, cell implantation, and cell-based gene therapy. Although several materials have been used for CM, alginate is considered to be quite effective. Alginate bead-containing cells can be prepared by extruding a cell–alginate mixture into a calcium chloride solution. It is possible to easily create calcium alginate (Ca-alginate) beads with a syringe. However, beads that are generated by syringes are not suitable for CM due to their large size (>1000 μm). Researchers have proposed a number of solutions for this problem. The use of certain equipment is an inseparable part of these solutions. This study demonstrated that small size (<400 μm) Ca-alginate beads can successfully be generated by modifying the syringe method. In this study, this method was successfully employed for CM and embryoid body (EB) formation in alginate.